Tinjauan perspektif ekologi politik: Persepsi masyarakat terhadap rencana pembangunan wisata premium di Taman Nasional Komodo, Pulau Komodo - Mongi, Elrin Meivian; Afifah, Fadhila; Fauziah, Rachma; Rahallus, Semuel (Ecotourism and Environment Conservation, 2024)
Introduction: The Komodo dragon (Varanus komodoensis) is a protected reptilian species found in the Komodo National Park (KNP). The Komodo National Park and its surrounding areas are among the National Strategic Areas (NSAs) listed in Government Regulation No. 13 of 2017 concerning the National Spatial Planning Plan. The KNP is currently planned by the government to become a super premium tourist Geopark. This research aims to understand the local community's perceptions of the development plan and whether there are impacts on natural capital in the Komodo National Park area as a result of this development. Result and Conclusion: Based on the research findings, it is found that this development has not fully involved the local community in its formulation. There are concerns among the local community regarding economic competition due to the planned development of premium tourism and concerns about environmental degradation and the threat of Komodo dragon extinction.